Pengaruh Financial Technology, Pengetahuan Investasi, Motivasi, Modal Minimal Dan Risiko Terhadap Minat Investasi Generasi Milenial - Revina Liani Komala Dewi; Endang Kartini; Rusdi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2023)
This research was conducted to determine the effect of financial technology, investment knowledge, motivation, minimum capital, and risk on the millennial generation's investment interest in Cakranegara District. This research is a quantitative research with an associative approach. The population of this study is the millennial generation aged 25-40 years, totaling 16,836 people. As many as 100 millennials aged 25-40 years who work as private employees are the samples in this study. Data was collected using a questionnaire which was then processed using SPSS 25 with multiple linear regression analysis methods. The results of this study indicate that financial technology, investment knowledge, and risk have no effect on the millennial generation's investment interest. Meanwhile, motivation and minimal capital have an effect on the millennial generation's investment interest. The results of this study also found that the independent variables namely financial technology, investment knowledge, motivation, minimum capital and risk had a 50% effect on investment interest as the dependent variable while 50% millennial generation investment interest was influenced by other variables outside this study.